Earnings, Size, and Book-to-Market Effects on Banking Stock Returns in Nepal - Rana, Surya Bahadur (Management Dynamics, 2021)
This study attempts to examine the effect of earnings, size, and book-to-market equity on common stock returns of banking sector firms in Nepal. Using the sample of 21 commercial banks in Nepal consisting of 231 firm-year observations over the 2010-2020 periods and based on the panel data fixed-effect estimation with AR(1) disturbances, the study reveals that earnings and size have significant positive effects on common stock returns of the banking sector in Nepal. However, the study reveals significant negative book-to-market equity effects on cross-sectional banking stock returns in Nepal. The positive earnings effect implies that banks with higher earnings yields have higher stock returns. Similarly, the positive size-effect implies that larger banks outperform the smaller banks in Nepal. Similarly, the negative book-to-market effect on common stock returns observed in this study implies that banks with lower value creation have lower stock returns.